Pelatihan Pembenahan Pembukuan Pada Usaha Roti Idola Bukittinggi - Hatta, Ermatati; Maretha Rissi, Dita; Maryati, Ulfi; Mustika, Rasyidah; Haslina, Welsi (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
Micro, Small and Medium Enterprises (MSMEs) have a role for the community in the midst of an economic crisis. By fostering MSMEs, it is believed that economic recovery can be achieved. Basically, MSMEs are mostly informal in nature and therefore tend to be easier for new entrepreneurs to enter. Accounting information has a very important influence on achieving business success, including for small businesses. Accounting information in the form of financial statements can be the basis for MSMEs to make decisions in managing small businesses, including market development decisions, price development, and others. Micro, Small and Medium Enterprises (MSMEs) are synonymous with the lack of awareness to run bookkeeping well in the business world. So that the bookkeeping and filing processes have not been carried out properly and result in a lack of accountability for activities every period. The purpose of this service is to provide training and improvement of bookkeeping and filing at the Idol Bread Business in the city of Bukittinggi. The expected outcome of this dedication is the existence of a bookkeeping process and the improvement of good filing for the sake of business continuity in the future.